Nilai pendidikan Moral Dalam Novel Harga Sebuah Percaya Karya Tete Liye - Pandiangan, Analisa Januati; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
The value of moral education is a value related to a responsible human person. The value of moral education aims to appreciate and respect humans as humans and treating humans as humans is the human obligation of every human being. Darmadi (2012: 51). Problems in this research: 1) What are the values of moral education and their relationship to the educational realm of Bloom's Taxonomy in the aspects of responsibility, conscience and obligation contained in the novel Harga a Confidence by Tere Liye. The theories used in this research are Bertens (2001), Kusniati (2012), Moleong (2018). The method the author uses is a descriptive method using content analysis techniques. The data collection technique was carried out using hermeneutic techniques. The results of this research show that the value of moral education in the novel Harga a Confidence by Tere Liye which is related to aspects of responsibility contains 15 data, for example; "He, like other lowly sailors, was tasked with preparing food, cleaning the ship and washing clothes, getting a share in the narrowest room." There are 30 data aspects of conscience, for example; "You're really good at playing it. Can you teach me?” The girl stared with sparkling eyes, just like a child who hopes for the promise of playing around." There are 7 data aspects of obligations, for example; “Girls must comply with arranged marriages. The marriage was carried out to strengthen relations between families." If the value of moral education is linked to the educational domain according to Bloom's Taxonomy, there are 32 examples of data in the cognitive domain; "A too brave nod from an orphaned young man, poor father, raised by the love of benefactors, uneducated, and too weak to dare to make decisions in life." 15 pieces of affective data, for example: "He, like other lowly sailors, was tasked with preparing food, cleaning the ship and washing clothes, getting a share in the narrowest room." Psychomotor 5 data examples: "Jim swallowed hard. Then he began to tell about his past of being poor, uneducated, weak and cowardly in the most beautiful city. Tells about his work as a violinist. The weddings he attended.